Komunikasi Agama dan Kearifan Lokal: Dimensi Pesan dan Saluran Komunikasi Agama Masyarakat Mamala Maluku - Pardianto, Pardianto (Jurnal Komunikasi Islam, 2017)
This article discusses the role of local culture as a channel of religious communication in conveying religious teachings in Mamala, Leihitu, Central Maluku, Maluku Province. Through descriptive qualitative methods, this study concludes that local tradition has remained an effective medium of religious communication for internalizing cultural values and Islamic teachings amongst Mamala villagers. The religious symbols embedded within the local culture, such as taking bath before Ramadan, the Shafar shower, the maulid ceremony of the Prophet Muhammad, the marriage and pregnancy ceremonies, tradition of pukul sapu lidi, the alifuru attraction, and the traditional dance Manuhua, have become religious communication channel, for religious leaders in particular, to meaning-making as well as to convey the 'new interpretation' of the symbols that is not in line with Islamic teachings.